Creative thinking in language learning classes: An analysis of educational policy in Moroccan public primary schools - Smare, Zaina; Elfatihi, Mohamed (Thinking skills and creativity, 2025)
•Moroccan educational policy documents lack a clear definition of creative thinking.•Creativity is primarily associated with artistic work.•In language classes, creativity is viewed as a higher comprehension skill, while in math and science, it is considered a higher-order cognitive skill linked to problem-solving.•No explicit guidance is provided on fostering creative thinking in classrooms, including language learning.•The study offers recommendations for better integrating creative thinking into language learning class. Creative thinking is considered one of the essential skills of the 21st century that should be promoted throughout the educational system, particularly in primary schools across all subjects, including language classes. The first step in effectively developing creative thinking in schools is to provide a curriculum with clear guidelines on how to foster this skill. Educational policy documents are of paramount importance because they outline the content and processes that should be communicated in the classroom. The current article reports the findings of an analysis of five Moroccan educational policy documents namely, The National Charter for Education and Training (1999), The White Paper (2002), The Strategic Vision of 2015–2030, The Framework Law 51–17 (2019), and The Primary Education Curriculum (2021). The analysis centers on two key questions: how creative thinking is defined and described in Moroccan educational policy documents, and how the importance of integrating this skill is articulated, particularly in the context of language learning classes. Our analysis reveals that educational policy documents do not offer a clear and operational definition of creativity, and the term is used differently across school subjects. The provided descriptions of the skill are all positive, suggesting that it is not perceived as a negative attribute. However, the documents do not offer guidance on how teachers should develop creative thinking. Additionally, educational policy documents often equate creativity with artistic production. This suggests that educational policy makers have a bias or preference for thinking mainly about artistic work when considering activities that promote creative thinking. The study concludes with practical recommendations for policymakers to effectively integrate the promotion of creative thinking in language education through educational policy documents.